Disposition kinetics and bone penetration of ampicillin and cefazolin during fracture repair in dogs - Singh, Balroop; Srivastava, A K; Sharma, S N (The Indian Journal of Animal Sciences, 2012)
Ampicillin and cefazolin were given intravenously @ 10mg/kg.b. wt. after repair of fracture with intramedullary pin.Following single intravenous administration the distributilm half-life (t1/2alfa) , elimination half life (t1/2beeta) and Vd (area) of ampicillin were 0.458hr. 3.27br and 0.625 L.kg-1, respectively, and for cefazolin 0.347hr, 2.03 hr and 0.333 L.kg-1, respectively. The concentration of ampicillin in muscle at 1 and 2 hr were 5.27±0.46 and 4.3±0.1 µg/g, respectively, and in bone at 2 hr was 4.38±0.13 µg/g. The level of cefazolin in muscle at 1 and 2 hr were 5.14±0.34 and 5.14±0.17 µg/g. respectively, and in bone at 2 hr 5.24±0.24 µg/g. Both the antibiotics are having sufficient penetration in bone and surrounding muscles and can be recommended in the management of bacterial infection during orthopaedic Surgery.